The Effect of Interfering Waves Strategy in Developing Some Basic Volleyball Skills for Intermediate First Graders (Medico Legal Update, 2021)
The research objectives to reveal the effect of using the interfering waves strategy in learning some basicskills in the game of volleyball (serve from the bottom facing, receiving the serve from the bottom, andpreparing from the top) for the first intermediate students, the researchers used the experimental method,and the research sample consisted of (32 A student with (16) students in each group, and by lottery twogroups were named to represent one of them the experimental group and the other the control group,and parity was achieved between the two groups in the variables (age, weight, and height) in addition toachieving parity between them in basic skills (under study), And the overlapping waves strategy was usedwith the experimental group players, but with the control group, the method was used by the trainer, and theimplementation of the experiment took nine weeks with two educational units per week for each group of18 educational units, and the time for one educational unit was (45) minutes, and the experiment started on10/2/2018 until 1/15/2019.The researchers used the following statistical method: the mean, standard deviation, simple correlationcoefficient (Pearson), (t) test for two related means and two equal samples, and (t) test for two unrelatedmeans and two equal samples. And after analyzing the data statistically, the researchers reached conclusions,the most important of which are:1. The use of the overlapping waves strategy had a clear role in learning some basic skills (under study)for the experimental group players.2. Take advantage of the overlapping waves strategy in physical education lessons for all school levels.